2019
DOI: 10.7554/elife.42214
|View full text |Cite
|
Sign up to set email alerts
|

A Gs-coupled purinergic receptor boosts Ca2+ influx and vascular contractility during diabetic hyperglycemia

Abstract: Elevated glucose increases vascular reactivity by promoting L-type CaV1.2 channel (LTCC) activity by protein kinase A (PKA). Yet, how glucose activates PKA is unknown. We hypothesized that a Gs-coupled P2Y receptor is an upstream activator of PKA mediating LTCC potentiation during diabetic hyperglycemia. Experiments in apyrase-treated cells suggested involvement of a P2Y receptor underlying the glucose effects on LTTCs. Using human tissue, expression for P2Y11, the only Gs-coupled P2Y receptor, was detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 84 publications
2
66
1
1
Order By: Relevance
“…However, ATP (via P2 receptors) or its degradation product adenosine (via P1 receptors) can also significantly contrib ute to its regulation in both white and brown adipocytes. 18,46 Notably, in our cells, ATP and BzATP have similar effect on calcium signals and lipolysis, indicating that the P2X7 re ceptor could mediate these processes, even though we cannot exclude a role for other P2 receptors, as reported in rat white adipocytes. 37,50 The degree of lipolysis inhibition by apyrase could be surprising, but to us, it indicates that the effect of isoproterenol on lipolysis is partially dependent on the release (and action) of endogenous ATP.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…However, ATP (via P2 receptors) or its degradation product adenosine (via P1 receptors) can also significantly contrib ute to its regulation in both white and brown adipocytes. 18,46 Notably, in our cells, ATP and BzATP have similar effect on calcium signals and lipolysis, indicating that the P2X7 re ceptor could mediate these processes, even though we cannot exclude a role for other P2 receptors, as reported in rat white adipocytes. 37,50 The degree of lipolysis inhibition by apyrase could be surprising, but to us, it indicates that the effect of isoproterenol on lipolysis is partially dependent on the release (and action) of endogenous ATP.…”
Section: Discussionmentioning
confidence: 45%
“…Adipocytes grown in high glucose medium, mimicking a hyperglycaemic state, displayed enhanced ATP release com pared to the normoglycaemic state. 46 Remarkably, insulin stimulation on its own did not affect ATP release, while it strongly inhib ited the adrenergically induced ATP release by stimulating the hydrolysis of cAMP via the signalling pathway that ac tivates PDE3 ( Figure 5). 46 Remarkably, insulin stimulation on its own did not affect ATP release, while it strongly inhib ited the adrenergically induced ATP release by stimulating the hydrolysis of cAMP via the signalling pathway that ac tivates PDE3 ( Figure 5).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Irrespectively of this however, PKA signaling has been generally linked with vasodilation, thus raising questions about the functional relevance, if any, of this kinase in the regulation of vascular LTCCs. Intriguingly, recent studies revealed that elevations in extracellular D-glucose (HG) potentiate LTCC activity via a G s /AC/PKA pathway in vascular smooth muscle [82][83][84][85]. This HG-induced PKA-dependent activation of LTCCs resulted in increased global [Ca 2+ ] i and vasoconstriction, thus providing the first example of a PKA-dependent pathway underlying vascular smooth muscle contraction.…”
Section: L-type Ca 2+ Channel Camentioning
confidence: 99%
“…The association of Ca V 1.2 with these signaling pathways is orchestrated by AKAP5 [86]. PKA (and perhaps PKC) augments L-type Ca 2+ channel Ca V 1.2 activity by increasing Ca V 1.2 phosphorylation at serine 1928 (pS 1928 ) [82,85] stochastic and persistent activity of LTCCs was modulated by membrane potential [92]. However, the occurrence of LTCCs with persistent activity is limited to specific regions of the surface membrane and has been demonstrated to be highly dependent on PKC activity and AKAP5 expression [81,86].…”
Section: Regulation Of Vascular Smooth Muscle Excitability By Voltagementioning
confidence: 99%